Strategi Peningkatan Rantai Nilai Agroindustri Daging Sapi - Shabrina, Nur; Syarief, Rizal; Arkeman, Yandra (Jurnal Aplikasi Manajemen, 2015)
The increasing demand of beef commodity in Indonesia must be supported by agood supply chain management to achieve self-sufficiency and food security. This study aimsto analyze consumers'expectations for commodity beef in Depok, identifying and mappingthe beef agro-industry value chain, and analyze strategic alternatives in order to enhancethe value chain agroindustry beef based on the characteristics of the livestock industry inDepok. The method used in this research is descriptive method with a case study approach.Based on analysis, 11 attributes was obtained to affect the quality of the beef ie. ratio of fat,flavor, color, marbling, juiceness, scents, halalness, freshness, price, texture, and availabilityin the market. The result of gap analysis showed that the actual conditions perceived byconsumers related quality of beef has not fulfilled consumers'expectations. In result of qualityhouse, strong relationships contained the halalness attributes. Moderate relationshipsare contained in the freshness and cutting process. Weak relationship found in all facilitiesin the technical characteristics. In the value chain analysis, identified two types of flowactivity. The results of the stakeholder analysis shows that the attributes of consumers andentrepreneurs have the same powerful and highest position compared with other stakeholders.